Tympanomastoidectomy for Cholesteatoma in Children: Audiometric Results. (October 2019) - Tzelnick, Sharon; Yaniv, Dan; Raveh, Eyal; Ulanovski, David; Hilly, Ohad
Objectives: The aim of this study was to investigate the audiometric outcomes of tympanomastoidectomy in children with cholesteatoma and to evaluate factors that may affect outcomes. Methods: A retrospective cohort study was conducted. All pediatric patients diagnosed with cholesteatoma who underwent primary canal wall-up tympanomastoidectomy with or without ossicular reconstruction from 2009 to 2016 at a tertiary university-affiliated pediatric medical center were included. Pure tone average (PTA) and air-bone gap (ABG) at 0.5, 1, 2, and 4 kHz were compared before and after surgery. Results: The cohort included 100 children (104 tympanomastoidectomies) of mean age 10.35 ± 3.6 years. The mean duration of follow-up was 35.4 ± 24.1 months. At surgery, 22 patients (21.2%) had intact ossicular chains, and 82 (78.8%) had ossicular discontinuity. Fifty-three patients (51%) underwent ossicular reconstruction, either partial (34 patients [64.1%]) or total (19 patients [35.8%]). In comparison with preoperative audiometry, there was a statistically significant improvement in PTA-ABG at the first postoperative examination (27.5 ± 12.7 vs 21.1 ± 11.1 dB, P = .001) and at the end of follow-up (20.2 ± 12.7 dB, P = .003) . Overall, values of less than 20 dB were measured in 34% of patients preoperatively and 73% postoperatively. On subgroup analysis, in patients who underwent any ossicular reconstruction, PTA-ABG was significantly improved relative to the preoperative value (28.1 ± 14.7 dB) at both the first (19.1 ± 11.9 dB, P = .006) and last (22.4 ± 15.1 dB, P = .011) audiometry examinations. Conclusions: Hearing outcomes after pediatric cholesteatoma surgery are diverse and related to several factors. The authors found that ossicular reconstruction improves audiometric outcomes, and the changes remain stable over time. Level of Evidence: IIB